Feminist Therapy - Laidlaw, Toni; Malmo, Cheryl (Canadian Journal of Counselling and Psychotherapy, 2011)
This article traces the roots of feminist therapy and its independence from traditional and prevalent theories and therapy practices. The authors assert that Freudian theory and humanistic assumptions are sexist and contribute to the powerlessness of women. In contrast feminist therapy, practiced with individuals or in groups, deals directly with client counsellor relationship, trust, advocacy and empowerment. In addition feminist therapists help clients consider stereotyping, expanding options, self-valuing, and acting on feelings, thoughts, intentions. The authors conclude this article with an excerpt from a client's experience of therapy.